The associations between intergenerational mobility of income and cognitive function in midlife–The Young Finns Study - Nurmi, Amanda; Vepsäläinen, Teemu; Pahkala, Katja; Puolakka, Elina; Pulkki-Råback, Laura; Elovainio, Marko; Juonala, Markus; Hutri, Nina; Kahonen, Mika; Lehtimaki, Terho; Jokinen, Eero; Laitinen, Tomi P.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Background: Systematically high and upward mobile (lower childhood and higher adulthood) socioeconomic status (SES) has been suggested to be associated with better overall cognitive function in adulthood compared to systematically low or downward mobile (high childhood and low adulthood) SES.
Methods: Participants' SES mobility was assessed using data on childhood family income (N = 3596, age 3-18) and own adulthood income (N = 1941, age 34-49). Adulthood learning and memory, working memory, information processing, and reaction time were measured using a computerized test. Altogether, 1804 participants had data on life-course income level and cognitive function in adulthood.
Results: Compared to participants with stable high income, those with stable low, downward, or upward mobile income had worse memory and learning, and information processing. Participants with stable low or downward mobile income had worse working memory and reaction time. The results persisted after adjusting for age, sex, childhood/adulthood lifestyle, cardiovascular risk factors, and polygenic risk score for cognitive function.
Conclusions: Individuals with stable high income may have better midlife cognitive function. This finding highlights the role of life-course SES for disparities in adulthood cognitive function. Understanding the role of early-life determinants of midlife cognitive function is important, as this knowledge may be applied to the early promotion of adulthood cognitive health.